Factors Associated with Non-Adherence to Antihypertensive Medication among Hypertensive Patients in Community - Shrestha, Tirtha Man; Bhusal, Laxman; Raut, Shankar; Ghimire, Rajan; Shrestha, Poonam (Journal of Karnali Academy of Health Sciences, 2019)
Objective: Hypertension is one of the common non-communicable health problems. While pharmacologic intervention is the most efficient way to control hypertension; non-adherence to medication is accounted as a significant cause for complications. This study was to address and to determine the magnitude of non-adherence among hypertensive patients by summarizing the associated risks factors among patients in community level. Method: This is a cross sectional study conducted on hypertensive patients who visited the community health clinic at Dhading, Nepal on 9th and 10th June 2018 using a pre structured questionnaire. Patients were sampled by nonprobability purposive sampling method. Effect of age, gender, marital status, employment, education level, presence of diabetes, cerebrovascular disease, current smoker, and family history of hypertension were analyzed by compliance of antihypertensive drugs using frequency distribution, chi-square test, and logistic regression. For all of the analysis p value <0.5 was considered as significance. Results: 150 patients were included in the study, out of whom 48 patients were found adherent and 102 patients non-adherent to antihypertensive medication. Out of total population 46% (n=69) were male and 54% (n=81) were female with no significant difference between compliant and noncompliant groups (OR= 1.512, p-=0.292). Mean age of patients in complaint group was 57 years and in non-compliant group was 52 years with odds ratio of 0.959 (p= 0.004, 95% C.I =0.933-0.987). However, there was no significant effect of marital status, employment status, and family history of hypertension on adherence to anti-hypertensive medication. Presence of diabetes had significant effect on adherence to medication (OR= 8.494, p= 0.014). The most common reason for non-adherence was the fear of getting stuck with medication for lifetime (n=31, 30.3%) followed by the use of ayurvedic/home remedy (n=27, 26.5%), unaware of complications (n=16, 15.7%), life style modification (n=14, 13.7%), and financial weakness (n=9, 8.8%). Pearson’s correlation of these reasons was between -1 to 0 with p value <0.5. Conclusion: Fear of taking medication lifelong was the major reason for non-adherence; however, age and comorbid health conditions like diabetes have a significant effect on adherence to medication. Health care awareness and counseling can help these patients to overcome the fear of taking medication for lifetime, which can increase the medication compliance rate.